An Egyptian oasis - Beadnell, H. J. L. (Hugh John Llewellyn), 1874-1944 (Salt Lake City, UT : Project Gutenberg, 2023)
"An Egyptian Oasis: An Account of the Oasis of Kharga in the Libyan Desert" by H. J. Llewellyn Beadnell is a scientific publication written in the early 20th century. The book provides a detailed investigation into the history, physical geography, and water supply of the Oasis of Kharga, a remote region nestled in the vast Libyan Desert. It targets readers with interests in archaeology, geography, and geology, shedding light on this unique environment and its inhabitants. The opening of the work introduces Kharga Oasis as an intriguing region accessed via recent railway connections from the Nile Valley. It describes the stark contrast between the lush Nile Valley and the surrounding arid desert, emphasizing the oasis's rich historical significance and distinct cultural identity, stemming from its ancient Libyan roots. Beadnell discusses the geological uniqueness of the area, touching on the underlying water supplies derived from deep aquifers, and hints at the ongoing struggle against natural elements like sand and wind that have historically shaped both the physical landscape and the livelihood of its people. This first glimpse sets the stage for a deeper exploration of the oasis's natural and anthropological history. (This is an automatically generated summary.)
The Libyan Desert and its oases -- Early records -- The roads leading to the oasis -- Topography and geology -- The northern villages -- The southern villages -- The oasis under Persian and Roman rule -- The extinct lakes of the oasis -- The underground water-supply -- Flowing wells: some experiments and observations -- The origin of the artesian waters -- The ancient subterranean aqueducts -- Boring methods: ancient and modern -- The contest between man and wind-borne sand -- Some economical aspects of the oasis -- Some notes on sport and natural history -- Appendix: Literature on the oasis of Kharga.
Release date is 2023-04-04
Galo Flordelis (This file was produced from images generously made available by The Internet Archive and the HathiTrust Digital Library)
Keywords: Water-supply -- Egypt -- Kharga (Oasis); Kharga (Egypt : Oasis)